THE ACQUISITION OF ENGLISH GRAMMAR MASTERY OF THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT TEACHER TRAINING AND EDUCATION FACULTY OF MAHASARASWATI DENPASAR UNIVERSITY IN ACADEMIC YEAR 2009/2010. - Murtini, Ni Made Wersi; Astawa, I Nengah (Jurnal Santiaji Pendidikan (JSP), 2011)
This study is focused on assessing the ability of the first semester students of English Department, Faculty of Teacher Training and Education of Mahasaraswati Denpasar University in academic year 2009/2010 in mastering English grammar. This study was intended to answer the Research Question: ‘To what extent is the acquisition of English grammar mastery of the first semester students of English Department, the Faculty of Teacher Training and Education Mahasaraswati Denpasar University in academic year 2009/2010?. The data required were collected by administering the valid and reliable research instrument in form of multiple choice test. Then, the data were analyzed by using Norm Reference Measures of five standard values. The population of the study is the first semester students of English Department in the Faculty of Teacher Training and Education Mahasaraswati Denpasar University which consists of 120 students. They are considered to have heterogeneous characteristics. There were 30 students determined as the sample of the study using quota random sampling technique. The result of the data analysis showed that (1) 13.33% out of the whole subjects under study showed excellent ability in mastering grammar, (2) 6.66% showed good ability, (3) 53.33% showed sufficient ability, (4) 23.33% showed insufficient ability , (5) 3.33% showed poor ability in mastering grammar. If the result of the study were used as the bases to assign level to the subjects under study, then 26.66% fail in learning and acquiring English grammar. It means that 26.66% of them still have low ability. The finding of the present study was trusted to have rather limited degree of validity and reliability because it was conducted using an ex post facto research design and it has some inherent independent variables which contaminate the validity and reliability of the findings. The findings of the study can be used as the bases in planning better language teaching especially in mastering grammar.